Performance analysis of LDPC channel coding in 4G systems - Khalifa, Othman Omran; Noralya Fatin, Noralya Fatin (Blue Eyes Intelligence Engineering & Sciences Publicatio, 2019)
Due to the degradation in wireless communication system by the burst errors in of fades under multipath environment, the efficient and the quality of received signals are questionable. Therefore, the error corrections are crucial part needed to satisfy the users. This paper focuses on performance analysis of channel coding in 4G systems. There are many codes, but this paper highlights on Viterbi Algorithm and LDPC codes with BPSK modulation and Additive white Gaussian noise(AWGN). The comparative performance of Viterbi algorithm and LDPC is explored in this paper. This comparison will be beneficial for next mobile communication system generations.